Tomato in Ghana: Summary of stakeholder dialogue - Robinson, Elizabeth J. Z.; Kolavalli, Shashidhara (International Food Policy Research Institute, 2010)
On 23 April 2010, farmers, traders, processors, agribusiness, Ghanaian and international academics, donors, and officials met in Accra for an exchange of views on how to revive the strategic but ailing tomato sector. The dialogue was organized by Ghana's Ministry of Food and Agriculture (MoFA) and the International Food Policy Research Institute (IFPRI), and centered around the presentation and discussion of a case study of the tomato sector in Ghana that addressed productivity, processing, marketing, and institutional support. The dialogue was an important step in an ongoing study of the tomato sector that involves a range of stakeholders, mirroring the diversity of the dialogue participants. The tomato case study, coordinated by IFPRI, is the result of contributions of many different stakeholders. The following individuals contributed directly: Kwabena Adu-Gyamfi (Afrique Link Ltd); Lydia Aforley Anum; Chris Lartey; Jones Okoe Tagoe; Kwame Owusu (Ghana National Tomato Traders and Transporters Assn); Aaron Attefa Ampofo (Meridian Agricultural Services); Samuel Asuming-Brempong (Agricultural Economics, University of Ghana); Stephen Awiti- Kuffuor (Independent consultant); Yakubu Balma (University of Development Studies); Dominic Fuachie-Sobreh (Savanna Agricultural Research Institute-CSIR); Emelia Monney (MoFA); John Ofosu-Anim (Crop Science, University of Ghana). The case study could not however have been prepared without the cooperation of many individuals and organizations who we met with over the past six months, including farmers, processors, and private sector companies (Upper East Vegetable Farmers Association and the Irrigation Company of Upper Region (ICOUR), for example).